Asuhan Keperawatan Kerusakan Intergritas Jaringan pada Ny.M dengan Ulkus Diabetes Militus di Ruang Edelweis Rsud Dr. R Goeteng Taroenadibrata Purbalingga - Wahyu Dwi Saputro; Suci Khasanah; Siti Haniyah (Seminar Nasional Penelitian dan Pengabdian Kepada Masyarakat, 2021)
Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia associated with abnormalities in carbohydrate, fat and protein metabolism caused by decreased insulin secretion or decreased insulin sensitivity or both, leading to chronic microvascular complications and neuropathy. Diabetic ulcers (sores) in DM patients are a sign of vascular complications and neuropathy. As in chronic ulcer patients in general, diabetic ulcer patients can feel a loss of sensation, easy trauma and skin damage, leg deformity and even hospitalization to amputation. This writing aims to describe nursing care for damage to tissue integrity in Mrs. M with diabetes mellitus (DM) ulcers in the Edelweis room of RSUD Dr. R Goeteng Taroenadibrata Purbalingga. Writing method: using a case study with a descriptive case study design that describes the nursing care provided to patients starting from assessment, formulation of diagnoses, intervention plans, implementation and evaluation.